Customer service delivery performance of globe store representatives in region 1 - Latoja, Mark Anthony D. (Saint Louis College : [s.n.], 2017)
This study assessed the customer service delivery performance of Globe Store Representatives in Region 1. Specifically, it determined their level of performance along job knowledge and skills, quality of work, quantity of work/Productivity, timeliness, and living out the Globe way; the level of customer satisfaction along the identified areas; the capabilities and constraints, and the relationship between; the level of performance and the customers' satisfaction. The descriptive method was used with three sets of questionnaires, administered to 519 respondents. It was found that the level of performance of the CSRs was very satisfactory and the customers were much satisfied on the five identified areas by CSRs. There was no significant relationship between the level of performance of CSRS and level of customer satisfaction. The five identified areas were identified as capabilities and a validated customer service delivery manual was recommended, among others.
Bibliography: pages 117-123.
CHED-La Union
Keywords: Customer relations